(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study was conducted to validate polymerase chain reaction (PCR) as a confirmatory diagnostic tool to find out the presence and frequency of Streptococcus agalactiae (S. agalactiae) and Streptococcus dysgalactiae (S. dysgalactiae) in mastitic milk samples obtained from dairy cows in the southern region of Bangladesh. Materials and Methods: A total of 196 samples of bovine milk were collected from various dairy farms in the Chattogram metropolitan area of the southern part of Bangladesh. DNA extracted from isolates obtained by culturing California mastitis test (CMT)-positive mastitic milk samples (n = 146) on 5% sheep blood agar was used as a template for PCR. Two sets of specific primers based on the 16S rRNA gene were used to discriminate between S. agalactiae and S. dysgalactiae. Four PCR products were subjected to sequencing, followed by phylogenetic analysis. Results: The PCR analyses revealed that out of the 146 CMT-positive milk samples tested, 29 samples were positive for S. agalactiae (19.86%), while 26 samples were positive for S. dysgalactiae (17.81%). Further sequence analysis of the corresponding PCR products and bioinformatics analysis verified the results. Conclusion: The study proves the efficiency of PCR as a useful diagnostic approach to determine the presence and prevalence of S. agalactiae and S. dysgalactiae in mastitic milk samples obtained from dairy cows. J. Adv. Vet. Anim. Res., 10(2): 178–184, June 2023 http://doi.org/10.5455/javar.2023.j667